The Role Of Management Accounting Practices In The Use Of The Mediate Relation The Quality Of Information And The Quality Of An Erp System On Performance Of Companies In Indonesia Manufacture - Farid Wajdi (Akuntabilitas, 2018)
The purpose of this research is to examine and analyze the role of management accounting practices in the mediated relationship influences the quality of the accounting information system and Enterprise Resource Planning systems (ERP) against the performance of the company. Design/ methodology/ approach to hypothesis testing using partial least square approach (PLS). We perform an empirical study against the 89 companies in Indonesia that use ERP systems. Findings indicate that management accounting practices could bring impact on company performance of 63.7%. In this study found the findings that accounting techniques used after the use of Enterprise Resource Planning systems (ERP) can affect the performance of the company amounting to 68.5%. The influence of the use of management accounting provides the mediation role against the improved performance of the company. Research limitations/ implications of this model indicates that the effect of the use of mediation practice of management accounting is an important variable for understanding how to utilize a system of Enterprise Resource Planning (ERP) exactly, but if not There is a push from Top management in accepting changes to it will not be achieved. The practical implications of adopting the system of Enterprise Resource Planning (ERP) systems integration and ensure that the impact on the business value. In order for the system of Enterprise Resource Planning (ERP) has a positive impact on the value of the business, the process of integration with the Enterprise Resource Planning system (ERP) should be ensured. Originality/ value – this research provide new knowledge about the importance of the use of contemporary management accounting practices used with Enterprise Resource Planning systems (ERP) to improve the performance of the company.